2022
DOI: 10.3390/biology11071011
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency in FTSJ1 Affects Neuronal Plasticity in the Hippocampal Formation of Mice

Abstract: The role of the tRNA methyltransferase FTSJ1 in the brain is largely unknown. We analyzed whether FTSJ1-deficient mice (KO) displayed altered neuronal plasticity. We explored open field behavior (10 KO mice (aged 22–25 weeks)) and 11 age-matched control littermates (WT) and examined mean layer thickness (7 KO; 6 WT) and dendritic spines (5 KO; 5 WT) in the hippocampal area CA1 and the dentate gyrus. Furthermore, long-term potentiation (LTP) within area CA1 was investigated (5 KO; 5 WT), and mass spectrometry (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…FTSJ1 is a member of the methyltransferase superfamily and is involved in ribosomal RNA processing and modification. FTSJ1 plays an important role in brain development and mutation of FTSJ1 is related to intellectual disability [12][13][14][15]. The role of FTSJ1 in cancer is elusive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FTSJ1 is a member of the methyltransferase superfamily and is involved in ribosomal RNA processing and modification. FTSJ1 plays an important role in brain development and mutation of FTSJ1 is related to intellectual disability [12][13][14][15]. The role of FTSJ1 in cancer is elusive.…”
Section: Discussionmentioning
confidence: 99%
“…Research has revealed the generation of diverse transcription variants through alternative splicing. Conditions linked to this gene are connected to cognitive impairment [12][13][14][15]. The impact of mutations or abnormalities in FTSJ1 on the efficiency of codon-specific translation and the plasticity of brain neurons has been confirmed through genetically modified mouse models [13,15].…”
Section: Introductionmentioning
confidence: 99%